2018
DOI: 10.1183/13993003.00545-2018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of WHO group 3 pulmonary hypertension in advanced idiopathic nonspecific interstitial pneumonia

Abstract: Pulmonary hypertension (PH) is associated with impaired quality of life, worsened functional status and increased mortality in idiopathic pulmonary fibrosis (IPF) [1]. The prevalence and clinical impact in other idiopathic interstitial pneumonias (IIPs) has not previously been reported. Given the prognostic significance of PH in IPF, we sought to determine the prevalence and severity of World Health Organization (WHO) group 3 PH in a cohort of patients with biopsy-proven idiopathic nonspecific interstitial pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Pulmonary hypertension is a major global health issue, with Group 3 PH prevalence on the rise affecting up to 60% of patients with chronic lung diseases 2,3 . Currently there are no disease-modifying therapies for PH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary hypertension is a major global health issue, with Group 3 PH prevalence on the rise affecting up to 60% of patients with chronic lung diseases 2,3 . Currently there are no disease-modifying therapies for PH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension (PH) is a devastating disease, affecting approximately 15-50 million people wor World Health Organization (WHO) Group 3 PH -PH secondary to chronic lung disease and/or hypoxia -is the leading cause of PH, with rising incidence globally and the highest mortality rate among all types of pulmonary v disease [2][3][4] . Group 3 PH patients, likewise, utilize the health care system up to four times higher than patients va 1 , Elnaz (STING), ons related cribed.…”
Section: Introductionmentioning
confidence: 99%
“…However, in idiopathic NSIP there is evidence that PH may be present in about one‐third of patients. 111 In patients with chronic hypersensitivity pneumonitis (chronic HP), precapillary PH may also be quite common (44%) 112 and similarly appears to be associated with a worse prognosis. 113 Furthermore, one study of chronic HP patients demonstrated that an increased PA/aorta ratio on CT is associated with worse survival.…”
Section: Phenotypes Of Ph In Ildmentioning
confidence: 99%
“…PH was reported in 31% of a cohort of 35 patients with idiopathic nonspecific interstitial pneumonitis and 44% of a cohort of 50 patients with chronic hypersensitivity pneumonitis. 126,127 More advanced parenchymal lung disease is associated with worse hemodynamics [128][129][130] and even echocardiographic PH 131 or minimal elevations in mPAP (>17 mm Hg) 132 are associated with reduced survival in patients with IPF. Interestingly, the degree of parenchymal lung involvement, based on PFTs 133 and high-resolution CT fibrosis score, 131,[134][135][136][137] does not correlate with PH severity.…”
Section: Epidemiology Of Group 3 Ph Due To Lung Disease And/or Hypoxiamentioning
confidence: 99%